ANALISIS KUALITAS PELAYANAN LABORATORIUM TERHADAP KEPUASAN MAHASISWA PENDIDIKAN BIOLOGI FKIP UNTAN - Aryati, Eka (Jurnal Kajian Pembelajaran dan Keilmuan, 2017)
AbstractThis research aimed to analyze student’s satisfaction on the quality of laboratory services in Biology Education. The exploratory research was used in this research. The subjects in this research are Biology Education’s students of FKIP Tanjungpura University. The data were collected using questionnaire with Likert scale. Data were analyzed to reveal the picture on the ground that were collected descriptively by interpreting the results of data processing through the tabulation. The results of this research are: (1) The level of students’s satisfaction to the services of laboratory/laboratory staff in the amount of 41.24% stated quite satisfied, 42.27% are satisfied, and 11.34% are very satisfied; (2) The level of students’s satisfaction to the service of lab assistant in the amount of 40.21% stated quite satisfied, 40.21% are satisfied, and 12.37% are very satisfied; (3) The level of students’s satisfaction to the equipment in the lab in the amount of 58.76% stated quite satisfied, 21.66% are satisfied, and 2.06% are very satisfied; (4) The level of students’s satisfaction to the lab materials in the amount of 52.58% stated quite satisfied, 22.68% are satisfied, and 2.06% are very satisfied; (5) The level of students’s satisfaction to the physical facilities and supporting laboratories in the amount of 46.39% stated quite satisfied, 22.68% are satisfied, and 5:15% very satisfied. Overall the level of student’s satisfaction to the laboratory services of Biology Education in FKIP Tanjungpura University is quite satisfied. Keywords: student’s satisfaction, laboratory services, quite satisfied.